THEOLOGICAL DIMENSIONS IN MEMITU RITUALS IN CIREBON - B Busro; Ai Yeni Yuliyanti; Abdul Syukur; Rifki Rosyad (Balai Pelestarian Nilai Budaya Jawa Barat, 2020)
Indonesia is very famous for its rich culture. Cirebon as one of the districts in West Java is also very thick with its culture. This article discusses one of the cultures in Kedungsana Village Cirebon, the phenomenon of ritual slametan Memitu. The purpose of this study is to examine the practice of ritual slametan Memitu carried out by Kedungsana community together with its theological dimensions. The research subjects were the community of Kedungsana Village, Plumbon District, Cirebon Regency. The process of collecting data through direct observation and to get deep information in interviews, we use a purposive sampling technique. The results of the study found that the purpose of carrying out the ritual slametan Memitu was as a manifestation of gratitude for all the favors that had been given from the